Designing For the Blind: Multisensory Design Approach for City’s Park - Nouvend Setiawan; Fadhil Faried Putra; Datin Intan Baktara; Zuhrotul M. Ula; Arina Hayati; Kirami Bararatin; Fardilla Rizqiyah; Collinthia Erwindi (Journal of Architecture & Environment, 2022)
A city is said to be accessible if its implementation accommodates users’ needs, including those with special needs, either disabled, elderly, children, etc. The environment is considered accessible if it ensures users' equality, equity, and living without a hitch. Surabaya, a city with great appreciation and recognition, known to be one of the best cities in the world, is still yet not to be entitled as an accessible city, despite all the greatness of the town, which improve the people living in it. Like most cities in Indonesia, Surabaya is built mainly normative oriented to buildings and urban infrastructures and facilities, not human-orientedapproach. Some failures in urban design implementation are common, for instance: tree roots and their placement are still interfering pedestrians on the sidewalk; most signage is still not informative enough for people with special needs in streets and public facilities; guiding blocks for blind people are far from decent to be safely and comfortably used in a daily basis; parks pay no attention to their accessibility; etc. This paper offers an idea about how to live as a blind person in Indonesia and how the experience is considered the primary part of a design process. The idea is generated to propose the design criteria for redesigninga public park. The data is gathered through participant observation by referencing from a blind’s point of view. Taman Bungkul is chosen as a field study as it is one of the best and the oldest parks in Surabaya and has been recognized and actively used by the residents. The proposed idea is formed by directly experiencing and observing what it feels like to be blind amidst public facilities designed for the non-disabled. The design criteria weigh how blinds gather information, percept spaces and distances, and use their senses such as aural, olfactory, tactile, and other senses. The result proposes design criteria for existing public facilities that are more accessible, visitable, comfortable, and inclusive for everyone, especially for the blind. The design is presented and graphically communicated.